Sobre a lei aplicável ao contrato de seguro perante o regulamento Roma I - Lima Pinheiro, Luis de (CUADERNOS DE DERECHO TRANSNACIONAL, 2012)
International insurance contracts raise the question of the determination of the applicable law. In the EU Member States (including in short term Denmark) the answer to this question is provided, in principle, by Rome I Regulation. This Regulation lays down a threefold choice of law system for international insurance contracts: insurance of large risks, insurance of mass risks situated in the EU and insurance of large risks situated outside the EU. Besides examining this choice of law system and the main interpretation problems arising therefrom, the article deals with its relationship with the Portuguese domestic choice of law rules contained in the Insurance Contract Act, and outlines a critical assessment as well as some proposals for its improvement.